Antifungal Activity of extracts from two Ouratea species on Candida albicans - de Araújo, Marcelo Francisco (2013)
Plants are invaluable sources of pharmaceutical products and Brazil, in particular, has yielded an incredible array of plant and animal products that have drawn the attention of ethnopharmacologists from around the world. Ouratea is a genus of tropical plants within the Ochnaceae. Ouratea is widespread throughtout the tropics, with species in Costa Rica, Brazil, Jamaica, and Kenya. The search for compounds with antimicrobial activity is urgent and indispensable for the treatment of infectious diseases caused by microorganisms resistant to traditional antimicrobial drugs. A screening was conducted with organic extracts from two species, from roots and leaves of Ouratea hexasperma var. planchonii Engl. and leaves and branches of Ouratea parviflora Engl., to identify plant extracts with antifungal properties against Candida albicans. Initially, minimal inhibitory concentrations (MICs) were determined in C. albicans cellular suspension in Sabouraud medium, in a range of 0.060-3.0 mg/ml. Fractions OHRMWE (Ethyl acetate fraction) and OHLMWB (Buthanol fraction) obtained by solvents partition of methanol:water extract from Ouratea hexasperma with ethyl acetate from the roots and n-butanol from the leaves, respectively, showed a higher antifungal activity. The antifungal activity of these extracts was also compared in growth delay of C. albicans cultures.